Imperfect Competition with Unknown Demand - Hadar, J.; Hillinger, C. (Review of Economic Studies, 1969)
Journal Article Imperfect Competition with Unknown Demand Get access J. Hadar, J. Hadar Case Western Reserve Search for other works by this author on: Oxford Academic Google Scholar C. Hillinger C. Hillinger University, Cleveland Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 4, October 1969, Pages 519–525, https://doi.org/10.2307/2296474 Published: 01 October 1969 Article history Received: 15 September 1967 Revision received: 15 April 1969 Published: 01 October 1969